2022
DOI: 10.3389/fneur.2022.918786
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Different Repetitive Transcranial Magnetic Stimulation Protocols for Stroke: A Network Meta-Analysis

Abstract: BackgroundAlthough repetitive transcranial magnetic stimulation (rTMS) has been proven to be effective in the upper limb motor function and activities of daily living (ADL), the therapeutic effects of different stimulation protocols have not been effectively compared. To fill this gap, this study carried out the comparison of the upper limb motor function and ADL performance of patients with stroke through a network meta-analysis.MethodsRandomized controlled trials (RCTs) on the rTMS therapy for stroke were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Therefore, HFrTMS-M1 may be more effective than LFrTMS-M1 in the convalescent phase of stroke. Xia et al (2022) also recommended the application of HFrTMS in patients with stroke patients during the convalescent phase.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, HFrTMS-M1 may be more effective than LFrTMS-M1 in the convalescent phase of stroke. Xia et al (2022) also recommended the application of HFrTMS in patients with stroke patients during the convalescent phase.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [ 55 ] summarized the effect of rTMS on the upper limb and fine motor function during various phases of stroke, and found that TBS was more effective than rTMS in the acute phase of stroke, while the opposite was true in subacute and chronic phase. Similarly, Xia et al [ 56 ] conducted a network meta-analysis that suggested that iTBS might be the preferred option for patients within one month from onset, whereas ≥ 10 Hz rTMS for mild stroke, severe stroke, and the convalescent phase. However, results should be interpreted with caution due to the relatively small sample sizes in some subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…While in TBS protocols, iTBS over the ipsilesional M1 was thought to yield better efficacy on the upper limb recovery than cTBS over the contralesional M1 ( Zhang et al, 2017 ), a finding that an ongoing meta-analysis will further investigate with the inclusion of more accumulating TBS studies ( Liu et al, 2019 ). On the other hand, a recent large network meta-analysis has revealed by probability ranking that among all the aforementioned protocols, the high-frequency (≥ 10 Hz) rTMS may be the most effective protocol for improving the upper limb motor function in stroke patients ( Xia et al, 2022 ).…”
Section: Motor Rehabilitationmentioning
confidence: 99%